(untitled) (Journal of Asian Development Studies, 2023)
This study explored the moderating effect of corporate image on service quality and customer satisfaction in franchises of healthcare laboratories in Pakistan. The service quality is discussed with its dimensions with the help of a tool called SERVQUAL, suggested by Parasuraman et al. 1994 and used by many researchers in the service sector. The service quality consists of three dimensions: Tangibility, Empathy, Responsiveness (dependent variables), and customer (patient) satisfaction (dependent variable), and the corporate image is considered to observe the moderating effect. The survey method using non-probability convenience is used for data collection, and bivariate correlation and multiple regression are considered in data analysis. The results exposed the laboratory’s image as a moderating variable to strengthen the relationship between service quality and patient satisfaction, and service quality’s effect on patients’ dignity regarding Pakistani health laboratories found irrelevant. This research work facilitates the health administrators, health care policymakers, and local and foreign investors to perceive a safer flight regarding good corporate image for increasing patient satisfaction required for expanding business as an entry mode strategy in each country’s healthcare system.